Making the World a Better Place to Live: African Research and Education Networks’ Contributions to the UN SDGs - Bowa, Harold; Amponsah, Effah; Al-Kouz, Yasmeen; Fiore, Silvia (AfricaConnect3, 2023)
In September 2015, 193 countries came together at the United Nations General Assembly (UNGA) and agreed on a blueprint to create a better and more sustainable world. They adopted the Sustainable Development Goals (SDGs), as ‘an urgent call for action by all countries - developed and developing - in a global partnership’1, designed to be realised by 2030. Since then, governments and non-governmental organisations alike have aligned their activities with the SDGs as a roadmap to making their impact on the development of the global society and also realise global relevance. This alignment has reaped benefits for both the global society and these governments and organisations, which include an increase in global influence and the ability to attract funding from the UN and other global funding organisations. Research and Education Networks (RENs) in Africa, both national (NRENs) and regional (RRENs) have also been contributing their best efforts to the achievement of the SDGs by helping to tackle urgent social issues and thereby creating value in several fields, including education, health, agriculture, gender equality, economic growth, and innovation. Unfortunately, this contribution has been largely, underreported. This paper seeks to contribute to remedying the situation by sharing evidence of the contribution to Africa and enhancing the visibility of the work done so far by the RENs.